Chronic Caffeine Treatment Protects Against α-Synucleinopathy by Reestablishing Autophagy Activity in the Mouse Striatum - Luan, Yanan; Ren, Xiangpeng; Zheng, Wu; Zeng, Zhenhai; Guo, Yingzi; Hou, Zhidong; Guo, Wei; Chen, Xingjun; Li, Fei; Chen, Jiang-Fan (Frontiers in Neuroscience, 2018)
Despite converging epidemiological evidence for the inverse relationship of regular caffeine consumption and risk of developing Parkinson's disease (PD) with animal studies demonstrating protective effect of caffeine in various neurotoxin models of PD, whether caffeine can protect against mutant α-synuclein (α-Syn) A53T-induced neurotoxicity in intact animals has not been examined. Here, we determined the effect of chronic caffeine treatment using the α-Syn fibril model of PD by intra-striatal injection of preformed A53T α-Syn fibrils. We demonstrated that chronic caffeine treatment blunted a cascade of pathological events leading to α-synucleinopathy, including pSer129α-Syn-rich aggregates, apoptotic neuronal cell death, microglia, and astroglia reactivation. Importantly, chronic caffeine treatment did not affect autophagy processes in the normal striatum, but selectively reversed α-Syn-induced defects in macroautophagy (by enhancing microtubule-associated protein 1 light chain 3, and reducing the receptor protein sequestosome 1, SQSTM1/p62) and chaperone-mediated autophagy (CMA, by enhancing LAMP2A). These findings support that caffeine—a strongly protective environment factor as suggested by epidemiological evidence—may represent a novel pharmacological therapy for PD by targeting autophagy pathway.